A novel requirement for DROSHA in maintenance of mammalian CG methylation. Issue 16 (3rd August 2017) - Stathopoulou, Athanasia; Chhetri, Jyoti B.; Ambrose, John C.; Estève, Pierre-Olivier; Ji, Lexiang; Erdjument-Bromage, Hediye; Zhang, Guoqiang; Neubert, Thomas A.; Pradhan, Sriharsa; Herrero, Javier; Schmitz, Robert J.; Ooi, Steen K.T.
Abstract: In mammals, faithful inheritance of genomic methylation patterns ensures proper gene regulation and cell behaviour, impacting normal development and fertility. Following establishment, genomic methylation patterns are transmitted through S-phase by the maintenance methyltransferase Dnmt1. Using a protein interaction screen, we identify Microprocessor component DROSHA as a novel DNMT1-interactor. Drosha -deficient embryonic stem (ES) cells display genomic hypomethylation that is not accounted for by changes in the levels of DNMT proteins. DNMT1-mediated methyltransferase activity is also reduced in these cells. We identify two transcripts that are specifically upregulated in Drosha- but not Dicer -deficient ES cells. Regions within these transcripts predicted to form stem–loop structures are processed by Microprocessor and can inhibit DNMT1-mediated methylation in vitro . Our results highlight DROSHA as a novel regulator of mammalian DNA methylation and we propose that DROSHA-mediated processing of RNA is necessary to ensure full DNMT1 activity. This adds to the DROSHA repertoire of non-miRNA dependent functions as well as implicating RNA in regulating DNMT1 activity and correct levels of genomic methylation.